Relationships between yield and its components in a diallel cross population of chilli - Soh, A. C.; Yap, T. C.; Graham, K. M. (Faculty of Agriculture, University of Malaya, 1976)
Correlation and path-coefficient analyses of the parents and hybrids 01 a u.allc: cross of chilli (Capsicum annuum L.) revealed that mosaic virus disease severn v :lau J m:ght!ilJle association with yield and positive associations with good agronomic traits. Iutal fruit nun- ber was a consistent principal component of yield.